<span>2/3 (x-7)= -2
x - 7 = -2 * 3/2
x - 7 = -3
x = -3 + 7
x = 4</span>
Answer:
x = 2, y = 1
Step-by-step explanation:
x + 4y = 6 and y = 3 - x have to be rearranged: x + 4y = 6 and x + y = 3
You subtract the equations to eliminate one of the variables (x) so that the other can be found
54•150,I think that’s the way to do it,let me know if I’m wrong.
Answer:
(x-1)²+ (y-0.5)²=6.25
Step-by-step explanation:
<u>The standard form of equation of a circle is;</u>
(x-a)²+(y-b)²=r² where (a,b) are the center of the circle and r is the radius
<u>Finding the mid-point of the given points</u>
(-1,2) and (3,-1)⇒midpoint will be 1/2(x₁+x₂) , 1/2(y₁+y₂)
midpoint= {1/2(-1+3), 1/2(2+-1)}
midpoint=(1,0.5)
<u>Finding the radius r; the distance from the center to either of the given two points</u>
Apply the distance formula d=√ (x₂-x₁)² +(y₂-y₁)²
Taking (x₁,y₁) as (1,0.5) and (x₂,y₂) as (-1,2) then
d=√ (-1-1)² +(2-0.5)²
d= √ (-2)²+(1.5)²
d=√4+2.25⇒√6.25⇒2.5
r=2.5
<u>Equation of the circle</u>
(x-1)² + (y-0.5)²=2.5²
(x-1)²+ (y-0.5)²=6.25
Answer:
x<3
Step-by-step explanation:
-5|1+2x|+6<-29
-5-10x+6<-29
-10x<-30
----- ----
-10 -10
x<3